Case report: cirrhosis and pregnancy (Research, Society and Development, 2025)
Objective: To report the case of a primiparous woman who discovered advanced chronic liver disease in the third trimester of pregnancy. Case report: Primigesta, 20 years old, 31 weeks of gestation, seeks an obstetric emergency service reporting abdominal pain, jaundice and pruritus of recent onset. The patient was hospitalized for tests. Ursodeoxycholic acid therapy was initiated due to suspected Benign Pregnancy Cholestasys. The tests showed a chronic liver, with suspicion of chronic hepatitis without previous diagnosis. The patient progressed with improvement of pruritus, but went into premature labor by cesarean section in the 32nd week, without major immediate complications. After 5 weeks, the patient returned to the health service for consultation with a hepatologist, presenting worsening jaundice, significant elevation of enzymes, and worsening of liver function. A liver biopsy was performed, suggesting overlap between cholestatic disease and autoimmune hepatitis. Conclusion: Although intrahepatic cholestasis of pregnancy was the diagnosis that led her to seek hospital care, the previously established liver disease aggravated maternal morbidity. Failure to diagnose liver disease early significantly impacted this patient's survival.